Pneumatologia w eklezjologii Konstytucji Lumen gentium Soboru Watykańskiego II z perspektywy teologii Yves’a Congara - Kasprzak, Artur Antoni (Poznańskie Studia Teologiczne, 2018)
For all readers of the text of the Lumen Gentium constitution of the Second Vatican Council during this event, and also immediately afterwards, it seemed that the document focused solely on the explanation of the Church from the perspective of Christ. Some of the conciliar observers, espe- cially the Orthodox theologians, brought up criticism that the reflection of the Council was marked by a Christomonism. This study presents the question of the pneumatological implications of the ecclesiology contained in the Lumen Gentium constitution from the perspective of Yves Congar’s theological thought. As the analysis of the undertaken research will show, the answer of the French theologian not only provides an essential response to the objection of Christomonism based on a direct commitment of this theologian to the co-writing of Lumen Gentium as early as March 1963, but it also gives a thorough insight into the subject-matter referring to his theological achievements already before and mainly after the Council. The Dogmatic Constitution on the Church has a dis- tinct pneumatological dimension. The theology contained therein is related to all the theses on the subject as they were formulated by Yves Congar in 1973.